Outcomes of Multidisciplinary Low-Vision Rehabilitation Using Two Questionnaires and the International Classification of Functioning, Disability, and Health - Suksri Chotikavanich; Akarawit Eiamsamarng; Thanaporn Layangool; Wichuda Krutthong; Siriwan Loket; Rungtip Yingyong; Somthin Dongngam; Waree Nujoi; Jaruwan Jai-ai; Nattapon Sarinak; Ekpipat Eksupapan; Saranya Sagan; et al. (Siriraj Medical Journal)
Objective: To evaluate the effectiveness of a low-vision service by using three tools and to identify the specific outcomes obtained from each instrument.